The role of automation in improving the performance of human resources: A field study on the employees of Al-Habib Real Estate Company - Mahdami, Afrah Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
Human resources automation enhances the efficiency of the human resources department, as it replaces manual human resources tasks with automated methods, allowing them to focus only on complex tasks such as decision-making and setting plans and strategies. The researcher's study aimed to identify the role of automation in improving the performance of human resources. The study sample consisted of 53 employees, and the results showed that about two-thirds of the sample (64.2%) are males, (58.5%) are Saudis, and (37.7%) are in the age group (25-29 years). And that (64.2%) of the respondents have an academic qualification (Bachelor’s degree), and (54.7%) of the respondents have a job title (employee). Results: 1. The study sample agrees with the reality of the application of automation and human resource management. 2/ That the study sample agree on the concepts of automating personnel affairs.3/ The study sample strongly agree that workers are highly aware of the characteristics and advantages of using automation. 4/ The study sample agreed that there are obstacles facing the application of automation. 5/ The study showed the weakness of the infrastructure in the companies. Study recommendations: 1. Adopting a project to develop the information technology infrastructure (hardware components, software and communication networks for the great advantages it provides, especially the improvement of operations paths in databases and human skills) due to the development of human resources management. 2. Work on developing the capabilities and skills of workers in the field of information technology by introducing them to training courses that enable them to deal with devices and modern communication networks. 3. Building a knowledge base (knowledge base) of employee preferences, emphasizing the importance of evaluating the value provided to the employee, collecting and updating those preferences on an ongoing basis, and working on an efficient investment of available information for all departments of the company. 4. Work on developing the organization's automation department, which in turn develops human resource management. 5. The company must make plans to develop human resources management.
Keywords: Automation; Human Resources; Al Habib Real Estate Company